On Optimal Control of Flat Hybrid Automata. Issue 2 (2020) - Zahn, Frederik; Kleinert, Tobias; Hagenmeyer, Veit
Abstract: Recently, Flat Hybrid Automata (FHA) were introduced as a new model class of hybrid systems. In order to answer the evident question of an optimal operation of the new class of FHA, a well-posed optimization problem definition for FHA is presented. This problem formulation also includes costs on discrete–state transitions and switching actions. We present a solution for a reduced problem: FHA with autonomous switching. For these, a new algorithm is introduced which solves the optimal control problem. The application of this optimization algorithm is shown with an electrical network example.